2017
DOI: 10.1002/celc.201600885
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Palladium Nanoclusters Encapsulated in Porous Carbon Nanosheets for Oxygen Electroreduction in Alkaline Media

Abstract: Ultrasmall noble-metal nanoclusters have been gaining extensive attention because of their unique catalytic activity. Herein, we describe a facile in situ method for the preparation of palladium nanoclusters encapsulated in porous carbon nanosheets as effective catalysts for the oxygen reduction reaction (ORR) in alkaline media. Structural characterizations through Xray diffraction, X-ray photoelectron spectroscopy, and transmission electron microscopy studies indicate that the Pd clusters were well incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The marriage of two metals can endorse both a geometric effect and an electronic effect. The geometric effect refers to the generation of a new catalytic active site due to the Encouraged by these findings, our group prepared Pd clusters in situ encapsulated in porous carbon nanosheets (CNS) for ORR in alkaline media [70]. Electrochemical tests showed that Pd/CNS-20% (Pd mass loading is 20%) displayed superior activity than Pd black, with mass activity five-times greater than Pd black [70].…”
Section: Alloyed Noble Metal Clusters For Orrmentioning
confidence: 99%
“…The marriage of two metals can endorse both a geometric effect and an electronic effect. The geometric effect refers to the generation of a new catalytic active site due to the Encouraged by these findings, our group prepared Pd clusters in situ encapsulated in porous carbon nanosheets (CNS) for ORR in alkaline media [70]. Electrochemical tests showed that Pd/CNS-20% (Pd mass loading is 20%) displayed superior activity than Pd black, with mass activity five-times greater than Pd black [70].…”
Section: Alloyed Noble Metal Clusters For Orrmentioning
confidence: 99%
“…For CS/CP, there are only two broad diffractions at 20-30°and 40-50°, which correspond to characteristic peaks of graphite. [26,27] In the typical Raman spectra of CS/CP and Mn 3 O 4 @CS/CP as shown in Figure 1b, there are two remarkable peaks at about 1036.2 and 1601.9 cm À 1 , which represent disordered carbon (D band) and graphitized carbon (G band), [28] respectively. The graphitization degree was judged through the I D /I G value.…”
Section: Materials Structure Characterizationmentioning
confidence: 99%
“…On the basis of our previous work of preparing porous carbon nanosheets (CNs) from metal-organic frameworks [36,37], herein, to the best of our knowledge, the Pd-Ru alloyed nanoparticles encapsulated in porous carbon nanosheets derived from MOFs were first fabricated and employed as a bifunctional electrocatalyst for both ORR and HER. By changing the variation of the Pd-to-Ru ratio, the composition and structure of the as-formed catalysts were fine-tuned.…”
Section: Introductionmentioning
confidence: 99%